Substance Dependence Treatment in Convicted Individuals in Prison - Nikolov, Jelena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
Research Problem: The treatment of substance dependence in convicted individuals involves various interventions, from therapeutic alternatives to incarceration, prison treatment, and reintegration programs. While much scientific attention is devoted to community-based addiction treatment programs, considerably less research has focused on prison programs. Convicted individuals who do not undergo addiction treatment are at a higher risk of mortality after release, repeated criminal offenses, lower employment rates, housing problems, and poor physical health. Objective: The study aims to comprehensively present the theoretical and empirical foundations in examining the treatment of substance dependence in convicted individuals in prison, their characteristics, motives, and other factors that sustain substance abuse in prison. It also explores efforts to improve treatment and presents research results and prevalence data. Methods: The research is based on a critical literature review, utilising theoretical analysis and synthesis of empirical findings. Discussion: Analysed research results indicate a high prevalence of substance abuse in prisons, ranging from 2% to 63%. If addictive behaviour is not treated, there is a high probability that the convicted individuals will revert to criminal behaviour. Some of the most effective treatment methods for convicted individuals dependent on psychoactive substances include cognitive-behavioural therapy and therapeutic communities. Conclusion: A review of empirical research and theoretical models suggests a need to pay greater attention to improving the quality of care and creating supportive systems from the entry of convicted individuals into prison to their release and integration into the community. It is recommended that all newly convicted individuals abusing psychoactive substances receive symptomatic treatment and therapy.